The Influence of Price, Service Quality and Trust on Consumer Loyalty in Trans Lamongan Straightforward Car Rental Services - Salshabilah, Falfida Mifta; Badriyah, Nurul; Rusminah, Sani; Azizah, Luluk Nur (Formosa Journal of Applied Sciences, 2024)
In this era of science and technology, business in the service sector is increasing rapidly. Many companies operate in any service sector. One of them in particular is transportation services. With the various facilities provided by the company, it has an impression on users or consumers. Price, service quality and trust can increase hope or what is meant by loyalty for consumers of the company's services. To determine the influence of price, service quality and consumer trust on customer loyalty in the Lamongan car rental industry. Quantitative methodology was used in this writing, which collected data from a sample of 101 respondents through distributing questionnaires as part of the survey. SPSS version 25 is the software used for analysis. In accordance with the findings of this paper, Consumer Loyalty (Y) is significantly and positively influenced by the variables Price (X1), Service Quality (X2), and Trust (X3).